Prefixal and postfixal parts as way of expression the matter of degrees meaning of the verbs in Ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article is devoted to research of detachable – postfixsalnyh formats on – + sia, vy, + sia, do – + – sia, z(s), – sia, u, -(v) + sia,ob,(obi) +sia, za-, sia, roz –(rozi) + sia, pry, + sia. As means of expression of gradation in modern Ukrainian. Lexems are anylysed with the above – mentioned formants and certainly grandee of tint that bring in the semantic structure of word.
Keywords: word-formation format gradosema; gradation (graduactor), grandee tint